An investigation into the influence of soil pattern on preferential flow and groundwater recharge in fractured bedrock and cover sand aquifers - Stander, McLachlan Du Toit (Stellenbosch : Stellenbosch University, 2011)
Thesis (MScAgric)--Stellenbosch University, 2011.